2015
DOI: 10.1089/aid.2014.0199
|View full text |Cite
|
Sign up to set email alerts
|

Targeting NF-κB Signaling with Protein Kinase C Agonists As an Emerging Strategy for Combating HIV Latency

Abstract: Highly active antiretroviral therapy (HAART) is very effective in suppressing HIV-1 replication and restoring immune functions in HIV-infected individuals. However, it fails to eradicate the latent viral reservoirs and fully resolve chronic inflammation in HIV infection. The ''shock-and-kill'' strategy was recently proposed to induce latent HIV expression in the presence of HAART. Recent studies have shown that the protein kinase C (PKC) agonists are highly potent in inducing latent HIV expression from the vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
121
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(121 citation statements)
references
References 62 publications
0
121
0
Order By: Relevance
“…hTNF-␣ acts by triggering intracellular signals that stabilize the NF-B transcription factor, allowing nucleus translocation. Once in the nucleus, NF-B can bind to the HIV-1 LTR region and promote HIV-1 transcription (38,39). In contrast, the RMD mechanism of action is focused on inhibiting HDACs that repress the HIV-1 LTR and help to initiate viral transcription (15).…”
Section: Resultsmentioning
confidence: 99%
“…hTNF-␣ acts by triggering intracellular signals that stabilize the NF-B transcription factor, allowing nucleus translocation. Once in the nucleus, NF-B can bind to the HIV-1 LTR region and promote HIV-1 transcription (38,39). In contrast, the RMD mechanism of action is focused on inhibiting HDACs that repress the HIV-1 LTR and help to initiate viral transcription (15).…”
Section: Resultsmentioning
confidence: 99%
“…NF-κB is free to enter the nucleus and bind to cognate binding sites in the viral LTR, inducing viral transcription. The role of targeting PKC-NF-κB signaling as a means to reactivate latent HIV-1 is shown in the Figure and has been reviewed in detail(29; 30). Among protein kinase C agonists, three chemical families are under active study: phorbol esters, including phorbol 12-myristate 13-acetate (PMA), prostratin and 12-deoxyphorbol 13-phenylacetate (DPP); macrocyclic lactones including bryostatin-1 and analogs; and diterpenes, which include ingenol compounds.…”
Section: T Cell Activating Agentsmentioning
confidence: 99%
“…Recent studies have identified the efficacy of PKC agonists including bryostatin-1 and ingenol derivatives in combination with LRAs from other mechanistic classes in vitro [12, 1921] as well as in vivo in a non-human primate model [22]. Activation of NF-kB signaling is thought to be the mechanism by which PKC agonists reactivate latent HIV-1 provirus [23, 24]. Cellular PKC isoforms activate transcription factors including NF-kB, AP-1 and NF-AT leading to T cell activation [2528].…”
Section: Introductionmentioning
confidence: 99%